Teachers’ Motivation in Pursuing Their Teaching Careers: Voices from Four In-Service EFL Teachers - Anna Riana Suryanti Tambunan; Widya Andayani; Isli Iriani Indiah Pane; Fauziah Khairani Lubis; Rasmitadila Rasmitadila; Mahmud Layan Hutasuhut (International Journal of Education and Learning, 2025)
This study listed factors that affect motivation among Indonesian English as Foreign Language (EFL) in-service teachers using the Maslow Hierarchy of Needs theory located at an urban secondary school in North Sumatera, Indonesia. Four Indonesian EFL in-service teachers had participated in this qualitative study, with interviews and observations used as primary methods in data collect ion. In this study, researchers found that fulfillment of educational background, feelings of love towards children, passion for becoming teachers, family inspiration, and religious reasons were motivational factors for teachers. From these findings, it can be concluded that teachers were self-motivated (intrinsic) and were not influenced by external factors. However, factor that negatively affected the motivation of teachers was working environment, mainly at school (extrinsic) level. These factors include having a big group of students in a classroom and extracurricular activities which resulted in students being tired, which could cause teachers to lack enthusiasm. Therefore, teachers require professional development to address self-actualization needs to excel in their competence.